Social Determinants of Health and Their Influence on Preterm Birth in Rural Indonesian Communities - Miranda Aisah; Tomiola Owkwulu; Winata Putri; Theresia Putri Sinaga; Syaifudin Syaifudin; Reza Andrianto (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Preterm birth (PTB), defined as birth before 37 completed weeks of gestation, is a major contributor to neonatal mortality and morbidity globally, with a disproportionate burden in low-resource settings like rural Indonesia. This study aimed to investigate the influence of social determinants of health (SDOH) on PTB in rural Indonesian communities. Methods: A retrospective cohort study was conducted using data from the Indonesian Maternal and Perinatal Health Survey (IMPHS) 2018-2021. A total of 15,480 women residing in rural areas with singleton pregnancies were included. SDOH variables examined included maternal education, socioeconomic status (SES), access to healthcare, and geographical remoteness. Multivariable logistic regression analysis was performed to assess the association between SDOH and PTB, adjusting for potential confounders. Results: The prevalence of PTB in the study population was 12.3%. Lower maternal education, lower SES, limited access to healthcare, and residing in remote areas were significantly associated with increased odds of PTB. Women with no formal education had 2.1 times higher odds of PTB compared to those with higher education (adjusted odds ratio [aOR] 2.1, 95% CI 1.8-2.5). Similarly, women in the lowest SES quintile had 1.8 times higher odds of PTB compared to the highest quintile (aOR 1.8, 95% CI 1.5-2.2). Conclusion: SDOH significantly influence PTB in rural Indonesian communities. Addressing these social inequities through targeted interventions, such as improving access to education, healthcare, and economic opportunities, is crucial for reducing the burden of PTB and improving maternal and child health outcomes.